Preserving Oocytes in Oncofertility. Issue 2 (17th January 2022) - McClam, Maria; Xiao, Shuo
Abstract: The prodigious rise of cancer survival rates enables many cancer survivors to live long lives. Therefore, the side effects of cancer treatments as well as the long-term quality of life after cancer have become more relevant. Ovarian toxicity is a major off-target effect of anticancer agents for childhood and young adult female cancer patients. Both chemotherapy and irradiation have been demonstrated to damage the ovary and increase the risks of premature ovarian failure (POF), early menopause, ovarian endocrine disorders, and sub- or infertility. Oncofertility is an emerging and multidisciplinary research and medical field that focuses on providing cancer patients with fertility preservation options. Oocyte quality and quantity are one of the most important factors to determine women's fertility success; therefore, preserving oocytes is paramount for maintaining the ability of young female cancer patients' reproduction after their recovery. This review summarizes peer-reviewed literature on current oocyte preservation options in oncofertility. We describe in-depth oocyte and embryo cryopreservation, ovarian suppression, ovarian tissue cryopreservation, in vitro maturation, ovarian transposition, and adjuvant therapy. Further, we discuss current guidelines and practices of female fertility preservation that cover preserving oocytes. Abstract : Preserving oocytes is fundamental for maintaining the ability of young female cancer patients' reproduction. Graphical Abstract: